Quality standard of traditional Chinese medicines: comparison between European Pharmacopoeia and Chinese Pharmacopoeia and recent advances - Fong Leong; Xue Hua; Mei Wang; Tongkai Chen; Yuelin Song; Pengfei Tu; Xiao-Jia Chen (BMC, 2020)
Abstract Traditional Chinese medicine (TCM) are becoming more and more popular all over the world. However, quality issues of TCM may lead to medical incidents in practice and therefore quality control is essential to TCM. In this review, the state of TCM in European Pharmacopoeia are compared with that in Chinese Pharmacopoeia, and herbal drugs that are not considered as TCM and not elaborated by TCM working party at European Directorate for the Quality of Medicines & Health Care (EDQM) but present in both European Pharmacopoeia and Chinese Pharmacopoeias are also discussed. Different aspects in quality control of TCM including origins, identification, tests and assays, as well as sample preparation, marker selection and TCM processing are covered to address the importance of establishing comprehensive quality standard of TCM. Furthermore, advanced analytical techniques for quality control and standard establishment of TCM are also reviewed.